TEKNOLOGI PENDEPOSISIAN FILM TIPIS METAL DENGAN METODE DC-SPUTTERING - Widodo, Selamet (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
In this paper described the results of testing and measurement of film thickness for target deposition Copper (Cu), Nickel-chromium (Ni-Cr) using DC-Sputtering, and shown a strong correlation between film thickness with time deposition by sputtering systems which are linear for each type of target. Characteristic curve is also shown on the pressure conditions of argon (Ar) constant, increasing the value of power from the starting 100 to 300 watts causes deposition while the value added to value of speeds from 350 to 450 watts, the value increased deposition nearly constant speed. And at constant power conditions, the addition of argon gas pressure (Ar) decreases the value deposition speed. By comparing each characteristic curve at the same pressure and power, connection speed deposition value comparison for each type of target are: Copper (Cu)> Nickel-chromium (Ni-Cr). Keywords: Deposition, Cu, Cr, Ni-Cr, DC-Sputtering.